Real-Time and Full-Scale Numerical Analysis and Monitoring of Displacements in the Left Bank of the Tabellout RCC Arch Dam during Construction and Operation, Jijel Province, Algeria - Houssam KHELALFA; Mustapha TEKKOUK; Hiba BEDJAOUI; Khalida TEBIZI (Journal of Materials and Engineering Structures)
This study provides a comprehensive evaluation of the Tabellout RCC dam in Jijel Province, Algeria, a unique structure classified as a combined gravity-arch dam. It addresses critical geotechnical, hydraulic and structural stability aspects, presenting significant contributions to the field of dam engineering by advancing the understanding of the interaction between RCC layers and adjacent slopes under operational conditions. This research employs real-time, full-scale numerical modelling using "Plaxis 2D," with a particular focus on arch behavior. The study bridges a gap by integrating hydrostatic and hydrodynamic pressures measured during the initial filling phase into the model, offering insights into the dam’s behavior under both static and dynamic conditions. Monitoring of RCC layers across three elevations prior to operation revealed minimal displacements, with a maximum recorded displacement of 1 mm in the critical interaction zone between the RCC and the left bank slope. Post-operation analysis demonstrated uniform deformation across elevations, with a negligible 1 mm variance, confirming the homogeneity of RCC stiffness—an essential factor for structural stability. The safety factor (FoS) analysis confirmed stability under static conditions, but highlighted vulnerabilities under seismic conditions, underscoring the need for enhanced resilience measures. This work extends findings from previous studies, particularly by validating the importance of a seismic belt at the foundation, through detailed numerical analysis and comparison with real-time monitoring data from PDL pendulums.